Evaporative cooling efficiency of pads consisting of vegetable loofah - Melo Júnior, Júlio César Ferreira de; Bamberg, João Victor Martins; Machado, Neiton Silva; Caldas, Emanuelly Nadja Gomes; Rodrigues, Marcos Sales (Comunicata Scientiae, 2019)
Brazilian agroindustry has presented constant innovations in the use of equipment and materials, among which are those that generate artificial thermal conditioning inside the zootechnical facilities, through a direct evaporative cooling system (DEC). In order to mitigate the effects of high temperatures associated with low air humidity in buildings in the northeastern region of Brazil, the use of DEC systems is evident. Therefore, DEC’s built with evaporative pads constituted of alternative materials, prove to be an interesting and viable alternative. The aim of this work was to evaluate the cooling efficiency of the evaporative pads constituted of vegetable loofah. The experiment was performed at the Campus de Ciências Agrárias, Federal University of the São Francisco Valley (UNIVASF) in Petrolina, Pernambuco state. The experimental design was in randomized blocks, in a 4x4 factorial scheme, with 13 replicates. Air temperature and relative humidity values were collected before and after the passage through the pad for different flow velocities and pad thicknesses, in order to calculate the evaporative efficiency. The variance analysis was significant at 5% probability for the sources of variation of the pad thickness (0.05, 0.075, 0.1 and 0.125 m) and the air flow rate (0.076, 0.264, 0.459 and 0.773 m s-1), and the interactions. The highest efficiency, 57.0% was observed for the interaction between the thickness of 0.125 m and the speed of 0.773 ms-1 as adjusted model.